How Much Do Lipid Guidelines Help the Clinician? Reading Between the (Guide)lines - Orringer, Carl E. (Methodist Debakey Cardiovasc J, 2019)
Although lipid guidelines provide updated, practical, and clinically relevant information that may be used in patient care, the continuing publication of new evidence and the inevitable treatment gaps present in all guidelines reinforce the importance of clinical judgment in shared decision making. This article explores the development of the 2013 American College of Cardiology/American Heart Association Blood Cholesterol Guidelines and the evidence base for managing patients with severe hypercholesterolemia, provides more recent high-quality evidence, and identifies existing treatment gaps that should be considered when caring for such patients. Although it was submitted prior to publication of the 2018 AHA/ACC/AACVPR/AAPA/ABC/ACPM/ADA/AGS/APhA/ASPC/NLA/PCNA Guideline on the Management of Blood Cholesterol, this review also includes key takeaway messages from the updated guideline.